Clay-hydrogen and clay-cushion gas interfacial tensions: Implications for hydrogen storage - Yekeen, N. (Elsevier Ltd, 2022)
Rock/fluid interfacial tension (Î³rockâfluid) govern the fluid flow dynamics, the injection/withdrawal rates, the gas storage capacity, and containment integrity during gas (H2, CO2, N2) geo-storage. Clay-gas interfacial tension (Î³clayâgas) data, especially for the clay-H2 (Î³clayâH2), the clay-N2 (Î³clayâN2) and the clay-CO2 (Î³clayâCO2) systems, have rarely been reported in the literature due to the challenging nature of these measurements in the laboratory. In this study, Neumann's equation of state and Young-Laplace equation was combined to compute clay-gas and clay-brine interfacial tensions (IFT) parameters at realistic geo-storage temperature (333 K) and pressure (5â20 MPa). Our results show that at similar thermodynamic conditions: Î³clayâH2 >Î³clayâN2>Î³clayâCO2. Our calculations also showed that: Î³kaoliniteâN2>Î³illiteâN2>Î³montmorilloniteâN2, and Î³kaoliniteâCO2>Î³illiteâCO2>Î³montmorilloniteâCO2. In contrast, for hydrogen a negligible difference in Î³clayâH2 was obtained for the three clay types, although, the IFT between clay minerals and brine in presence of hydrogen is different for these three clay types. Overall, computed Î³clayâH2 values were higher than Î³clayâN2 and Î³clayâCO2 values, whereas computed clay-brine interfacial tension was lower in presence of hydrogen compared to carbon dioxide and nitrogen. These results suggest that nitrogen and carbon dioxide could be used as favorable cushion gas for maintaining formation pressure during underground hydrogen storage. We also demonstrated a remarkable relationship between clay/gas IFT and gas density that could serve as a helpful tool for quick estimation of rock-fluid interfacial tension. Â© 2022 Hydrogen Energy Publications LLC